Differential visceral blood flow in the hyperdynamic circulation of patients with liver cirrhosis. Issue 9 (7th March 2016) - McAvoy, N. C.; Semple, S.; Richards, J. M. J.; Robson, A. J.; Patel, D.; Jardine, A. G. M.; Leyland, K.; Cooper, A. S.; Newby, D. E.; Hayes, P. C.
Summary: Background: With advancing liver disease and the development of portal hypertension, there are major alterations in somatic and visceral blood flow. Using phase‐contrast magnetic resonance angiography, we characterised alterations in blood flow within the hepatic, splanchnic and extra‐splanchnic circulations of patients with established liver cirrhosis. Aim: To compare blood flow in splanchnic and extra‐splanchnic circulations in patients with varying degrees of cirrhosis and healthy controls. Methods: In a single‐centre prospective study, 21 healthy volunteers and 19 patients with established liver disease (Child's stage B and C) underwent electrocardiogram‐gated phasecontrast‐enhanced 3T magnetic resonance angiography of the aorta, hepatic artery, portal vein, superior mesenteric artery, and the renal and common carotid arteries. Results: In comparison to healthy volunteers, resting blood flow in the descending thoracic aorta was increased by 43% in patients with liver disease (4.31 ± 1.47 vs. 3.31 ± 0.80 L/min, P = 0.011). While portal vein flow was similar (0.83 ± 0.38 vs. 0.77 ± 0.35 L/min, P = 0.649), hepatic artery flow doubled (0.50 ± 0.46 vs. 0.25 ± 0.15 L/min, P = 0.021) and consequently total liver blood flow increased by 30% (1.33 ± 0.84 vs. 1.027 ± 0.5 L/min, P = 0.043). In patients with liver disease, superior mesenteric artery flow was threefold higher (0.65 ± 0.35 vs. 0.22 ± 0.13 L/min, P < 0.001), while total renal blood flow was reduced by 40% (0.37 ± 0.14 vs. 0.62 ± 0.22 L/min, P < 0.001) and total carotid blood flow unchanged (0.62 ± 0.20 vs. 0.65 ± 0.13 L/min, P = 0.315). Conclusions: Rather than a generalised systemic hyperdynamic circulation, liver disease is associated with dysregulated splanchnic vasodilatation and portosystemic shunting that, while inducing a high cardiac output, causes compensatory extra‐splanchnic vasoconstriction ‐ the 'splanchnic steal' phenomenon. These circulatory disturbances may underlie many of the manifestations of advanced liver disease.